A characterization of local nilpotence for dimension two polynomial derivations. Issue 5 (4th May 2022) - Pan, Ivan
Abstract: Let k be an algebraically closed field. We prove that a polynomial k -derivation D in two variables is locally nilpotent if and only if the subgroup of polynomial k -automorphisms which commute with D admits elements whose degree is arbitrary big.